Risk-Based Investment Management in Practice - Cowell, Frances. (Global Financial Markets Series, 2013)
A practitioner's account of how investment risk affects the decisions of professional investment managers. Jargon-free, with a broad coverage of investment types and asset classes, the non-investment professional will find this book readable and accessible.